The Influence of Service Quality, Brand Trust, and Advertising on the Purchase Decision during the Covid-19 Pandemic - Tumpal Janji Raja Sitinjak; Tony Sitinjak; Abdulah Rakhman; Matthew Tio Devin Suryawan (Universitas Pendidikan Ganesha, 2023)
The rapid development of technology and the internet today supports all online-based businesses, including transportation service businesses. One of the online ojek transportation services in Indonesia is GoRide from the Gojek application platform. The selective attitude of customers and limited public mobility during this pandemic has resulted in tighter competition because many other brands provide similar services. Therefore, this study aims to analyze the influence of service quality, brand trust, and advertising on the purchase decision of GoRide services from Gojek during the COVID-19 pandemic in Jakarta. The data collection technique used in this study was a communication technique through the distribution of questionnaires electronically through Google Forms to 192 respondents. The sampling technique used is a non-probability sampling technique with a judgement sampling approach. The results of this study show that service quality has no influence on purchasing decisions. While brand trust and advertising have a positive and significant influence on purchasing decisions. The implications of this research highlight the importance of building and maintaining brand trust as well as effective advertising strategies to improve customer purchasing decisions.